Epigenome-wide meta-analysis of prenatal maternal stressful life events and newborn DNA methylation - Kotsakis Ruehlmann, Anna; Sammallahti, Sara; Cortés Hidalgo, Andrea P.; Bakulski, Kelly M.; Binder, Elisabeth B.; Campbell, Megan Loraine; Caramaschi, Doretta; Cecil, Charlotte A. M.; Colicino, Elena; Cruceanu, Cristiana; Czamara, Darina; Dieckmann, Linda; et al. (Molecular psychiatry, 2023)
Prenatal maternal stressful life events are associated with adverse neurodevelopmental outcomes in offspring. Biological mechanisms underlying these associations are largely unknown, but DNA methylation likely plays a role. This meta-analysis included twelve non-overlapping cohorts from ten independent longitudinal studies (N = 5,496) within the international Pregnancy and Childhood Epigenetics consortium to examine maternal stressful life events during pregnancy and DNA methylation in cord blood. Children whose mothers reported higher levels of cumulative maternal stressful life events during pregnancy exhibited differential methylation of cg26579032 in ALKBH3. Stressor-specific domains of conflict with family/friends, abuse (physical, sexual, and emotional), and death of a close friend/relative were also associated with differential methylation of CpGs in APTX, MyD88, and both UHRF1 and SDCCAG8, respectively; these genes are implicated in neurodegeneration, immune and cellular functions, regulation of global methylation levels, metabolism, and schizophrenia risk. Thus, differences in DNA methylation at these loci may provide novel insights into potential mechanisms of neurodevelopment in offspring.